Sex-specific associations of muscular fitness with overall academic performance and specific school subjects in adolescents: the EHDLA study - Manzano-Sánchez, David; Gutiérrez-Espinoza, Héctor; López-Gil, José Francisco (Frontiers in Psychology, 2024)
Introduction: Overall, muscular fitness and academic performance are two variables widely studied in the literature. However, evidence about the relationship between muscular fitness and specific school subjects (e.g., physical education) is scarce. Objective: The aim of this study was to examine the associations between muscular fitness and overall academic performance and between muscular fitness and specific subjects (i.e., language, math, foreign language, and physical education) in a sample of secondary Spanish school students. Methods: For the present study, a sample of 766 students (45% boys; aged 12 to 17 years) from the Eating Healthy and Daily Life Activities (EDHLA) study was used. An ALPHA-FIT battery was used to determine handgrip strength and lower body strength. The performance of the different school subjects was provided by the school centers. Results: Overall, for both boys and girls, greater muscular fitness was associated with greater academic results, with the greatest differences in physical education. However, only significant differences were identified for girls. Discussion and conclusion: Global strength is important for contributing to cognitive development, both in physical education and in the rest of the subjects of the educational curriculum for adolescents, especially because of its relationship with academic performance and physical education performance.